Seismological Evidence for Girdled Olivine Lattice‐Preferred Orientation in Oceanic Lithosphere and Implications for Mantle Deformation Processes During Seafloor Spreading. (19th October 2022) - Russell, J. B.; Gaherty, J. B.; Mark, H. F.; Hirth, G.; Hansen, L. N.; Lizarralde, D.; Collins, J. A.; Evans, R. L.
Abstract: Seismic anisotropy produced by aligned olivine in oceanic lithosphere offers a window into mid‐ocean ridge (MOR) dynamics. Yet, interpreting anisotropy in the context of grain‐scale deformation processes and strain observed in laboratory experiments and natural olivine samples has proven challenging due to incomplete seismological constraints and length scale differences spanning orders of magnitude. To bridge this observational gap, we estimate an in situ elastic tensor for oceanic lithosphere using co‐located compressional‐ and shear‐wavespeed anisotropy observations at the NoMelt experiment located on ∼70 Ma seafloor. The elastic model for the upper 7 km of the mantle, NoMelt_SPani7, is characterized by a fast azimuth parallel to the fossil‐spreading direction, consistent with corner‐flow deformation fabric. We compare this model with a database of 123 petrofabrics from the literature to infer olivine crystallographic orientations and shear strain accumulated within the lithosphere. Direct comparison to olivine deformation experiments indicates strain accumulation of 250%–400% in the shallow mantle. We find evidence for D‐type olivine lattice‐preferred orientation (LPO) with fast [100] parallel to the shear direction and girdled [010] and [001] crystallographic axes perpendicular to shear. D‐type LPO implies similar amounts of slip on the (010)[100] and (001)[100] easy slip systems during MOR spreading; we hypothesize that grain‐boundary sliding during dislocation creep relaxes strain compatibility, allowing D‐type LPO to develop in the shallow lithosphere. Deformation dominated by dislocation‐accommodated grain‐boundary sliding (disGBS) has implications for in situ stress and grain size during MOR spreading and implies grain‐size dependent deformation, in contrast to pure dislocation creep. Plain Language Summary: Earth's upper mantle is composed primarily of the mineral olivine, which responds to deformation by organizing its seismically fast axis in the flow direction. During seafloor spreading, olivine crystals align with the spreading direction and become frozen into the lithosphere preserving the near‐ridge deformation history. The resulting rock fabric can be observed in place via the directional dependence of seismic wavespeeds (seismic anisotropy) as well as in hand‐sample rocks collected from the field. However, interpreting seismic anisotropy observations in the context of laboratory and field data remains a challenge, due to large differences in length scale and incomplete seismic constraints. Here, we bridge this observational gap by incorporating multiple data types to solve for the complete anisotropic structure of oceanic lithosphere that formed ∼70 Myr ago. By comparing our model to laboratory data, we infer the magnitude of shear strain and style of olivine deformation during seafloor spreading for the first time. Our results indicate large shear strains and an olivine fabric type different to that typically assumed, consistent with deformation that is sensitive to the presence of grain boundaries even though most of the strain is produced by dislocations. This has new implications for the formation and evolution of oceanic plates. Key Points: We develop an in situ elastic tensor for oceanic lithosphere that incorporates co‐located compressional and shear wavespeed anisotropy constraints Seismic anisotropy is consistent with corner flow during spreading and shear strains of 250%–400% Girdled D‐type olivine fabric implies activation of multiple olivine easy slip systems during mid‐ocean ridge spreading